Anesthetic Management and Perioperative Complications in Endovascular Interventions: The Turkish Experience - Ezgi Erkilic; Elvin Kesimci; Cihan Doger; Tulin Gumus; Abdullah Yalcin; Orhan Kanbak (Global Journal of Anesthesiology - Peertechz Publications, 2015)
Background and Aim: Thoracic, abdominal and thoraco-abdominal aortic pathologies have highest mortality and morbidity causing pathologies in cardiovascular surgery. Co-existing diseases and age significantly increase risk of anesthesia and mortality rate in treatment of these patients. Endovascular techniques are used increasingly due to minimally invasive approach, decreased anesthesia risk during implementation, reduced length of hospital stay, and low mortality and mobidity rates. The aim of this investigation was to report our anesthetic experiences in endovascular techniques performed at our center. Materials and Methods: We evaluated 120 (19 females, 101 males; mean age: 67±12 years) consecutive symptomatic patients with thoracic and abdominal aortic pathologies who underwent endovascular stent graft surgery with either general or regional anesthesia or sedoanalgesia between 2009 and 2014, at our center. Results: The number of patients having abdominal endovascular stent graft surgery was 81. Among the rest; 87% underwent thoracic endovascular aneurysm repair, while 13% had both of the interventions. The duration of anesthesia and surgery was not different among the intervention groups. 86.8% of patients had general anesthesia, while 12.3% and 0.9% had regional anesthesia and sedoanalgesia; respectively. Postoperatively, the rate of being intubated and the length of stay in intensive care unit were found significantly lower in endovascular aortic repair (EVAR) group.  Conclusion: EVAR should be considered as a beneficial alternative treatment option for high-risk and inoperable, elderly patients. Anesthesiological approach to be selected in these patients may be affected not only by general condition and cooperation of the patient, but also by the location of the pathology and duration of the process. Thus, the anesthesiologists should be prepared to face issues related to the patient's safety both during the administration of anesthesia and in the postoperative period.